Study of the structural and electronic properties of valproic acid and new derivatives used as anticonvulsant agents - Comelli, Nieves Carolina; Lobayan de Bonczok, Rosana María; Castro, Eduardo Alberto; Jubert, Alicia Haydeé (American Chemical Society, 2011)
The conformational and electronic characteristics of the polar O9dC8—X10 moiety in the anticonvulsant valproic acid (Vpa) drug and some of their amides and ester derivatives are analyzed at the B3LYP level using the 6-31þG(d,p) and 6-311þþG(d,p) 6d,10f basis sets. Exploring the delocalization of the electron density of the O9dC8—X10 moiety by means of ELF, NBO, and AIM calculations, we found that the bending away from coplanarity of the atoms in O9dC8—X10 is accompanied by a three-dimensional arrangement of donor and acceptor proton units closing nearly planar pseudorings of four, five, and six members arising from stabilizing interactions around the O9dC8—X10 backbone. From the structure-property relationship analysis, we explain the origin of the change in the structural parameters and atomic charges in the polar moiety.